2014
DOI: 10.1186/1471-2202-15-66
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of a gamma-secretase inhibitor for hearing restoration in a guinea pig model with noise-induced hearing loss

Abstract: BackgroundNotch signaling plays a crucial role in the fate determination of cochlear progenitor cells, hair cells, and supporting cells in the developing cochlea. Recent studies have demonstrated the temporal activation of Notch signaling in damaged mature cochleae, and have demonstrated the induction of new hair cells by pharmacologically inhibiting Notch signaling. The present study aimed to illustrate the feasibility of pharmacologically inhibiting Notch signaling by using a gamma-secretase inhibitor for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…The result demonstrated the successful transdifferentiation of supporting cells to hair cells that were functional (38). Similar findings were recently reported by Tona et al (41). …”
Section: In Vivo Transdifferentiation Of Supporting Cells To Hair Celsupporting
confidence: 93%
See 1 more Smart Citation
“…The result demonstrated the successful transdifferentiation of supporting cells to hair cells that were functional (38). Similar findings were recently reported by Tona et al (41). …”
Section: In Vivo Transdifferentiation Of Supporting Cells To Hair Celsupporting
confidence: 93%
“…Transdifferentiation approaches have now been tested with small molecules with the goal of future clinical use (38, 41). We successfully induced hair cells using LY411575, a potent γ-secretase inhibitor (Fig.…”
Section: In Vivo Transdifferentiation Of Supporting Cells To Hair Celmentioning
confidence: 99%
“…Nevertheless, various approaches may be able to overcome this problem. Following on from promising work using Notch inhibitors in embryonic or neonatal systems, two studies have shown that localised treatment with inhibitors of Notch signalling can rescue both outer hair cell number (via direct transdifferentiation of supporting cells) and some limited hearing function in the noise-damaged mature mammalian cochlea [49,50]. Indeed, the importance of Notch signalling in the regenerative process has been underlined by a comprehensive transcriptome analysis of the regenerating chick utricle [51].…”
Section: Sensory Hair Cell Regenerationmentioning
confidence: 97%
“…Building on these findings, two recent studies examined the damaged neonatal mouse cochlea and demonstrated a similar ability of supporting cells to regenerate nascent hair cells after Notch inhibition (Bramhall et al, 2014;Korrapati et al, 2013). This pharmacological approach has also been applied to the damaged, mature mammalian cochlea, but yielded a significantly less robust regenerative response (Mizutari et al, 2013;Tona et al, 2014); unlike the effects observed in the zebrafish lateral line system and chick cochlea, the regenerated hair cells were attributed to direct transdifferentiation of supporting cells, as no cell proliferation was found. Although it is commonly postulated that the regeneration of a functional organ of Corti requires the coordination of supporting cell proliferation and hair cell differentiation such that a balanced ratio of sensory and non-sensory cell types is maintained, a modest functional improvement was observed using this pharmacological approach (Mizutari et al, 2013).…”
Section: Kip1mentioning
confidence: 99%